A molecularly engineered split reporter for imaging protein-protein interactions with positron emission tomography - Massoud, Tarik F; Paulmurugan, Ramasamy; Gambhir, Sanjiv S (Nature medicine, 2010)
Tarik Massoud and colleagues offer a new, noninvasive molecular imaging technique based on split reporter complementation for quantifying and imaging protein-protein interactions—cytoplasmic and nuclear— in vivo using positron emission tomography. They use a split reporter system based on the enzyme herpes simplex virus type 1 thymidine kinase, an approach designed to significantly improve the sensitivity and dynamic range of imaging protein-protein interactions. Improved techniques to noninvasively image protein-protein interactions (PPIs) are essential. We molecularly engineered a positron emission tomography (PET)-based split reporter (herpes simplex virus type 1 thymidine kinase), cleaved between Thr265 and Ala266, and used this in a protein-fragment complementation assay (PCA) to quantify PPIs in mammalian cells and to microPET image them in living mice. An introduced point mutation (V119C) markedly enhanced thymidine kinase complementation in PCAs, on the basis of rapamycin modulation of FKBP12-rapamycin-binding domain (FRB) and FKBP12 (FK506 binding protein), the interaction of hypoxia-inducible factor-1α with the von Hippel-Lindau tumor suppressor, and in an estrogen receptor intramolecular protein folding assay. Applications of this unique split thymidine kinase are potentially far reaching, including, for example, considerably more accurate monitoring of immune and stem cell therapies, allowing for fully quantitative and tomographic PET localization of PPIs in preclinical small- and large-animal models of disease.